2021
DOI: 10.1186/s12886-021-02115-x
|View full text |Cite
|
Sign up to set email alerts
|

IgG4-related disease in patients with idiopathic orbital inflammation

Abstract: Background To identify the prevalence of positive IgG4 immunostaining in orbital tissue among patients previously diagnosed with nongranulomatous idiopathic orbital inflammation (IOI) and to compare the clinical characteristics of patients with and without IgG4-positive cells. Methods A retrospective review of all patients with a histopathologic diagnosis of IOI was performed. Immunohistochemical staining was performed to identify IgG-positive cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 39 publications
0
7
0
7
Order By: Relevance
“…The usual recommended initial dose is 1 mg/kg/day, although higher doses are used for patients with intractable disease in the form of optic nerve involvement or active orbital myositis or those with evidence of systemic disease. [ 38 ] A dose less than 10 mg is ineffective for maintaining remission[ 39 ] [ Figure 7 ].…”
Section: U Pdated T Reatment S ...mentioning
confidence: 99%
“…The usual recommended initial dose is 1 mg/kg/day, although higher doses are used for patients with intractable disease in the form of optic nerve involvement or active orbital myositis or those with evidence of systemic disease. [ 38 ] A dose less than 10 mg is ineffective for maintaining remission[ 39 ] [ Figure 7 ].…”
Section: U Pdated T Reatment S ...mentioning
confidence: 99%
“…The ophthalmologic clinical hallmark of IgG4-related ocular disease is bilateral lacrimal gland enlargement with three features: suborbital nerve enlargement [7], exophthalmos, and compressive optic neuropathy [4]. IgG4-related optic neuropathy is commonly caused by compression of the optic nerve by enlargement of the lacrimal glands or other intraorbital tissues [4,[8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…A review of 55 previously diagnosed cases of OP demonstrated that over 40% were histologically re‐classified as IgG4‐ROD. In another study, which evaluated cases of previously diagnosed OP, the radiologic findings of bilateral orbital involvement and infraorbital nerve involvement are associated with IgG4‐ROD when tissue samples are assessed by IgG4‐ROD criteria 957,958 …”
Section: Benign Orbital Tumors and Lesionsmentioning
confidence: 99%